PENERAPAN MODEL PEMBELAJARAN INKUIRI PADA PEMBELAJARAN TEMA 7 SUB TEMA 2 PEMBELAJARAN 4 UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SDI TAUANAS - Un Lala, Sofia G; Koro, Maxsel; Fay, Sarah Densi (Journal of Character and ELementary Education, 2023)
This research aims to improve student learning outcomes by changing the learning process using the Inkuiri learning model. This research uses the classroom action research method which was held at SD Inpres Tauanas, with the results of the research showing that in cycle I, as many as 6 students (30%) from 20 subjects completed with an average score of 80 because they always focused their attention, were always active in class, always be responsible in carrying out group assignments, and be orderly during the teaching and learning process. Meanwhile, 14 other people and 20 subjects (70%) have not reached the standard of completion, because students do not understand the inquiry learning model. Most students play, lack attention when discussing, lack confidence in presenting work results, and lack responsibility in group assignments. given by the teacher. Furthermore, in cycle II student learning outcomes increased, namely from 20 subjects getting an average score of 96.99, 20 students completed with 100% completeness because they always focused their attention, were active in class, more confident when discussing and conveying the results of the discussion, and always responsible. responsible in carrying out group assignments, and being orderly during the teaching and learning process. Based on the results of the research above, it can be concluded that in applying the inquin learning model with theme 7 sub-theme 2 material, it can improve student learning outcomes and is in accordance with the minimum completeness criteria expected by the researcher.